ANALISIS PEMAHAMAN KONSEP GREEN CONSTRUCTION PADA PEMBANGUNAN GEDUNG KONSTRUKSI - PUTU ANANDA RAGA UTAMA; NI NYOMAN INTAN SAWITRI SARASWATI; TJOKORDA ISTRI PRAGANINGRUM; NI LUH MADE AYU MIRAYANI PRADNYADARI; IDA BAGUS SURYATMAJA; I GUSTI AGUNG GDE SURYADARMAWAN (GANEC SWARA, 2023)
Green construction is an effort or strategy for managing construction activities, including the use of efficient and environmentally friendly resources so that they can support a sustainable movement. However, in reality not all parties related to construction activities understand what is meant by green construction. In this regard, a study was conducted to find out how the understanding of construction actors, especially contractors, in the application of green construction. The research was conducted on the Gianyar Market development project because this project has the desire to apply the green building concept. The method used is a qualitative method with interviews, with respondents who are involved in the construction process of the Gianyar Market development. From the results of the study, it was found that the level of understanding of the informants on green construction was sufficient. The resource persons did not fully understand the aspects and factors as well as indicators in green construction. This can be seen from several key statements stating that the explanation of green construction is still general, including green construction which is environmentally friendly construction, does not pollute the environment, and minimizes the negative impact of construction on the environment. From the contractor side, it still requires a more detailed understanding related to green construction. Furthermore, socialization and training can be carried out, as well as strengthening the interpretation of related regulations to increase understanding of green construction.